Discourse Analysis as a Qualitative Approach to Study Information Sharing Practice in Malaysian Board Forums - Alice Shanthi; Lee Kean Wah; Denis Andrew D. Lajium (Penerbit UMS, 2015)
There are numerous approaches to qualitative research, and discourse analysis is one of them. The study of naturally occurring language in any social context is discourse analysis, and it makes use of various qualitative methods to increase our understanding of human experience. The researchers build upon Herring’s (2004) work, which used discourse analysis approach to explore communication taking place in mediated environment using Computer-Mediated Discourse Analysis (CMDA) toolkit. In this article the researchers will discuss how to conduct a study using the discourse analysis approach in computer-mediated environment specially in discussion board forums by analyzing the naturally occurring asynchronous communication using Herring’s CMDA toolkit to reveal how language is used to perform the many actions needed to share and exchange information online.